(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In the article, in order to ensure the quality of education, it begins with the identification of the necessary results of education. A competent approach is the quality of education in the modern education system. A competent approach is a ministry of students. Educational activity is important.